2019
DOI: 10.1634/theoncologist.2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying Outcomes: Checkpoint Inhibitor Combinations in First-Line Non-Small Cell Lung Cancer

Abstract: Purpose Lung cancer is one of the most common types of cancer, resulting in approximately 1.8 million deaths worldwide. Immunotherapy using checkpoint inhibitors has become standard of care in advanced non‐small cell lung cancer (NSCLC), and there is increasing interest in further improving outcomes through combination with other therapeutics. This systematic review evaluates emerging phase III data on the efficacy and safety of checkpoint inhibitor combinations as first‐line treatment for advanced NSCLC. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…However, inconsistent results have been obtained with these agents when given as monotherapy for second-line treatment in patients with EGFR-positive disease [61][62][63][64], and it therefore remains to be determined whether they are appropriate for use in patients with driver mutations. Combining immune checkpoint inhibitors with pemetrexed could improve outcomes [65], providing a potential therapeutic option following the development of TKI resistance. Indeed, several ongoing clinical studies are assessing the benefits of such combination treatment in patients with EGFR-positive advanced nonsquamous NSCLC who progressed after TKI therapy [66][67][68].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, inconsistent results have been obtained with these agents when given as monotherapy for second-line treatment in patients with EGFR-positive disease [61][62][63][64], and it therefore remains to be determined whether they are appropriate for use in patients with driver mutations. Combining immune checkpoint inhibitors with pemetrexed could improve outcomes [65], providing a potential therapeutic option following the development of TKI resistance. Indeed, several ongoing clinical studies are assessing the benefits of such combination treatment in patients with EGFR-positive advanced nonsquamous NSCLC who progressed after TKI therapy [66][67][68].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Conventional cytotoxic chemotherapies promote anticancer immunity through the release of tumor-associated antigens and/or depletion of immunosuppressive cells ( 26 , 27 ). Chemotherapy regimens in tandem with ICIs have been extensively studied and have become treatment options for NSCLC, triple-negative breast cancer and urothelial carcinoma ( 28 31 ). Similar to chemotherapy, radiation treatment can augment the anticancer immune response through the release of tumor antigens and modulation of the TME ( 21 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Impassion130 study demonstrated that first-line treatment with atezolizumab and nab-paclitaxel resulted in an overall survival benefit in patients with advanced programmed death-ligand 1 (PD-L1) positive TNBC, and this is a new standard of care (Schmid et al, 2020). Meanwhile, immune checkpoint blockade also advances the treatment outcomes for other cancer types including melanoma (Long et al, 2016), non-small cell lung cancer (Melosky et al, 2020), and renal-cell carcinoma (Motzer et al, 2019). However, not all patients experience therapeutic benefit from immunotherapy.…”
Section: Introductionmentioning
confidence: 99%